Examining the drivers of business cycle divergence between Euro Area and Romania - Ionut Jianu (Theoretical and Applied Economics, 2020)
This research aims to provide an explanatory analyses of the business cycles divergence between Euro Area and Romania, respectively its drivers, since the synchronisation of output-gaps is one of the most important topic in the context of a potential EMU accession. According to the estimates, output-gaps synchronisation entered on a downward path in the subperiod 2010-2017, compared to 2002-2009. The paper demonstrates there is a negative relationship between business cycles divergence and three factors (economic structure convergence, wage structure convergence and economic openness), but also a positive relationship between it and its autoregressive term, respectively the GDP per capita convergence.
Keywords: C32; O47; F44; F45; L16; 330; output-gap; business cycles; divergence; Euro Area; Romania